2020
DOI: 10.1001/jamanetworkopen.2020.10383
|View full text |Cite
|
Sign up to set email alerts
|

Association of Do-Not-Resuscitate Patient Case Mix With Publicly Reported Risk-Standardized Hospital Mortality and Readmission Rates

Abstract: IMPORTANCE The Centers for Medicare and Medicaid Services's (CMS's) 30-day risk-standardized mortality rate (RSMR) and risk-standardized readmission rate (RSRR) models do not adjust for do-not-resuscitate (DNR) status of hospitalized patients and may bias Hospital Readmissions Reduction Program (HRRP) financial penalties and Overall Hospital Quality Star Ratings. OBJECTIVE To identify the association between hospital-level DNR prevalence and conditionspecific 30-day RSMR and RSRR and the implications of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The existence of “do not resuscitate” orders has increased with time [ 142 ], although a wide range of prevalence has been reported [ 143 , 144 , 145 ]. Only very few guidelines on writing DNR orders—the “when and how”—are available, e.g., by professional medical societies [ 21 ].…”
Section: Relative Contraindications To the Initiation Of Ecmomentioning
confidence: 99%
“…The existence of “do not resuscitate” orders has increased with time [ 142 ], although a wide range of prevalence has been reported [ 143 , 144 , 145 ]. Only very few guidelines on writing DNR orders—the “when and how”—are available, e.g., by professional medical societies [ 21 ].…”
Section: Relative Contraindications To the Initiation Of Ecmomentioning
confidence: 99%
“…Numerous quality measures central to charting hospital performance can be examined using these files, including 30-day readmissions, mortality, home discharge, and compli-cations following total hip or knee arthroplasty, to name a few notable examples. As an illustration, Pollock et al utilized the SAFs to examine the association of the do-not-resuscitate patient case mix with risk-standardized hospital mortality and readmissions rates that are publicly reported 7 .…”
Section: Strengths and Best Uses Of Medicare Administrative Claims Datamentioning
confidence: 99%
“…Using national Medicare data, the study by Pollock and colleagues showed that higher hospital prevalence of a do-not-resuscitate (DNR) status that is present on admission (POA) may be associated with higher risk-standardized mortality rates but lower risk-standardized readmission rates across several clinical conditions, leading to a lower likelihood of penalization under the Centers for Medicare & Medicaid Services Hospital Readmissions Reduction Program (HRRP). The authors recommended that hospital prevalence of POA DNR status should be included in pay-for-performance risk-adjustment calculations.…”
mentioning
confidence: 99%
“…The implicit assumption is that hospitals with low prevalence of POA DNR status unfairly receive penalties, whereas hospitals with high prevalence of POA DNR status inadvertently get rewarded by the HRRP. Pollock and colleagues should be applauded for their thoughtful, well-designed analysis and their desire to improve performance measures. However, it is important to critically appraise their assumption that including POA DNR prevalence in risk-adjustment models will improve the ability to accurately and fairly assess quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation